Food Security in Rural Areas of Vaishali District, India: A Household Level Analysis - Sajjad, Haroon; Nasreen, Iffat (European Journal of Sustainable Development, 2014)
Food security has been one of the major developmental objectives in India. Though India has sufficient food production yet the achievement did not percolate down to households. This paper reports on an investigation into the food security status in Vaishali district of Bihar. Data were gathered across 16 administrative divisions in the district and eventually 959 farmers’ households were sampled using stratified random sampling techniques. This allowed computing composite food security index to assess the relative status of food security of the sampled farmers. The findings revealed that 75 % of the sampled households have low food security. Within farmers’ categories, most of the large farmers had high food security. Medium farmers experienced moderate food security while semimedium, small and marginal farmers were having low food security. Bivariate regression analyses between food security and its components of all the farmers shows food availability has a major impact on food security as 93 % variation in food security is explained by variation in food availability. The study suggested that priority should be accorded for creating rural employment opportunities, providing infrastructure for increasing production and creating awareness of education for long term sustainability of food security in the study area. Key words : Food security components, Food security, India